ANALISIS TRANSHIPMENT PASAL 69 AYAT (3) PERATURAN MENTERI KELAUTAN PERIKANAN NO. 30 TAHUN 2012 TENTANG USAHA PERIKANAN TANGKAP - Amelya Gustina (Faculty of Law, Universitas Jenderal Soedirman, 2014)
This study aims to analyze the content analysis of the application of Article 69 paragraph (3) of the Regulation of Minister of Marine Affairs and Fisheries No. 30 Year 2012 on Business fisheries in Regional Fisheries Management of the Republic of Indonesia to Indonesian marine fisheries. Previous studies or research focused on handling of legal issues and marine fisheries which was only viewed from the macro side perspective while this research mainly discusses transshipment as stipulated in Article 69 paragraph (3) Regulation of the Minister. It employed normative juridical method by qualitative-descriptive approach. The results showed that the application of the article led to an increased possibility of the practice of IUU fishing by foreign vessels in Indonesian waters, hence, a review of the implementation of the Article is necessarily conducted.Keywords: content analysis, marine fisheries, transhipment